Analisis Pengaruh Kualitas Pelayanan Yang Dimediasi Oleh Perceived Value Terhadap Keputusan Pembelian Ulang Pengguna Kartu Perdana Telkomsel - Ni Ketut Murdani; Ni Wayan Ardani; Kadek Pradnya Prayoga (Jurnal Ilmiah Satyagraha, 2020)
This study purposed to analyze the influence of mediated service quality perceived value on consumer repurchase decisions, and the difference between the effect of service quality and the effect of perceived value on the decision to repurchase Telkomsel starter cards. The sample in this study were 100 students from Denpasar City who used Telkomsel starter cards. By using the Convenience sampling method. The data analysis technique used in this study is multiple regression analysis.The results of this study prove that service quality is not too influential on the decision to repurchase Telkomsel starter cards because consumers think more about the value of benefits than the services provided when using  Telkomsel starter cards. Consumers only use services that are needed and if the service benefits them. There is a significant relationship between perceived value and the decision to repurchase Telkomsel starter cards.